Kajian Pengaruh Ukuran Penambat Pada Fermentasi Etanol Secara Continue dengan Batu Apung Sebagai Media Penambat Pada Fermentor Kolom Fixed Bed - Ronny Kurniawan; S.Juhanda S.Juhanda; Hany Figurhawa; Muhhamad Gandi (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Ethanol production is increasing every year due to the great need. Ethanol is widely used as chemicalsynthesis ingredient, as a solvent and can be used as a fuel mixture of gasoline, there by ethanol become analternative renewable fuel. Difficulties often encountered in the fermentation process, namely the separationof the product of yeast used. Tethered cell method (immobilized cell) may be one method that can be used asan alternative, and pumice can be used as an immobilized media. The purpose of this study was todetermine ethanol concentration and value of ethanol yield in the continues fermentation process usingcoloumn fixed bed fermenters with pumice as an immobilized cell media and comparing with free cellcondition. The parameters in this study is glucose concentration of 150 g / L with a temperature of 34 ° C,pH 4.5, substrat flow rate of 0,555 mL/min , pumice height is 50% fermentor height, and the number of cellsthat is tethered. While the variable in this study include the condition of the cell that is free and immobilized ,pumice size with mesh 6/8 and mesh 16/18 . Results obtained with the best conditions on a continuousethanol fermentation in a fixed bed column was obtained on condition of immobilized cells with a pumice sizemesh 16/18 with ethanol consentrasion of 61.8 % v/ v, the value of ethanol yield at 23,22% w / w and theaverage percentage of cells that escape 0.213%.